Analisis Kebutuhan Bahan Ajar Bahasa Inggris Berbasis Local Learning pada Siswa Sekolah Dasar - Oktariyani; Rani Puspa Juwita (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2020)
Abstract: This article aims to present the results of the analysis of the need for English language teaching materials in elementary schools based on local learning. The data in this article was collected through a questionnaire filled out by two English teachers and 26 third grade students at SD Negeri 09 Duren Tiga, South Jakarta, odd semester, 2018/2019, then analyzed using descriptive analysis. Objects of study in this article include: 1) suitability of KI and KD, 2) teaching materials used by teachers, and 3) teacher and student needs related to Local Learning-based teaching materials. The results show that: 1) All materials in teaching materials are in accordance with KI and KD 2) Teachers and students use other materials besides books from school to help in understanding a material; and 3) Teachers and students need teaching materials based on Local Learning that can be used to learn noun and adjective material. Thus, it can be understood that teaching materials based on Local Learning are needed. Keywords: Analysis, Materials, English, Local Learning.